Essays on the History of Mechanical Engineering - Sorge, Francesco; Genchi, Giuseppe (History of Mechanism and Machine Science, 2016)
This book treats several subjects from the History of Mechanism and Machine Science, and also contains an illustrative presentation of the Museum of Engines and Mechanisms of the University of Palermo, Italy, which houses a collection of various pieces of machinery from the last 150 years. The various sections deal with some eminent scientists of the past, with the history of industrial installations, machinery and transport, with the human inventiveness for mechanical and scientific devices, and with robots and human-driven automata. All chapters have been written by experts in their fields. The volume shows a wide-ranging panorama on the historical progress of scientific and technical knowledge in the past centuries. It will stimulate new research and ideas for those involved in the history of Science and Technology.